2007
DOI: 10.1002/job.503
|View full text |Cite
|
Sign up to set email alerts
|

The interactive relationship of competitive climate and trait competitiveness with workplace attitudes, stress, and performance

Abstract: SummaryThere has been a considerable debate about the individual and organizational benefits of competition. Adopting a person-environment fit perspective, this research examined the influence of competition as an interaction between trait competitiveness and competitive climate. Using a sample of information technology workers, competitive climate was considered as both an individual level variable and a workgroup variable. Results show that the effect of competitive climate depended on trait competitiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
218
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(256 citation statements)
references
References 46 publications
9
218
1
8
Order By: Relevance
“…According to this perspective, competition promotes less favorable sides of people, such as egoism for example. There are also studies indicating that competitiveness may not improve performance after all [42,51,52].…”
Section: Previous Research About Worry Indifference and Competitivenessmentioning
confidence: 93%
See 3 more Smart Citations
“…According to this perspective, competition promotes less favorable sides of people, such as egoism for example. There are also studies indicating that competitiveness may not improve performance after all [42,51,52].…”
Section: Previous Research About Worry Indifference and Competitivenessmentioning
confidence: 93%
“…On the one hand, there is the view that competitiveness is a good thing that makes people do their best [45]. According to social comparison theory [46] it is consistent with western culture to compare oneself to others in order to affirm one's own competence [see also 47,42]. Thus, according to this line of thought, competition is both something that people like to engage in, and something that improves their performance.…”
Section: Previous Research About Worry Indifference and Competitivenessmentioning
confidence: 94%
See 2 more Smart Citations
“…Barankay (2010) discovered that when freelance employees are ranked between each other, they are found to have reduced their work effort and are more likely to quit. Therefore, it is hypothesised that: H1: Competitive psychological climate is positively related to turnover intention Fletcher, Major, and Davis (2008) found that competitive psychological climate is negatively related to organisational commitment among information technology professionals with low competitiveness trait. A competitive climate at the workplace is expected to weaken one's commitment to the organisation because such a climate motivates one to leave the organisation (Arhab et al, 2013;Barankay, 2010;de Meis et al, 2003).…”
Section: Competitive Psychological Climatementioning
confidence: 98%